2018
DOI: 10.1002/slct.201702661
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Room Temperature Synthesis of Large Silver Nanoplates with Low Cytotoxicity

Abstract: In this work, a simple, fast, and room temperature aqueousphase route was developed to synthesize highly aniotropic silver (Ag) nanoplates with controllable sizes from 1 to 17 mm. Our simple synthetic protocol involves the direct reduction of polyethyleneimine (PEI) stabilized silver chloride (AgCl) nanoparticles with hydrogen peroxide (H 2 O 2 ) in the presence of pyrrolidone in an aqueous-phase at room temperature for short reaction time of 10 min. In the growth mechanism study, we found that the AgCl nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Silver nanoplate morphology was first prepared in triangular form by a photoinduced method from synthesized silver nanospheres . Since then, many different synthesis methods have been developed, such as other light irradiation methods, , biomimetic synthesis, and micelle directed synthesis, ,, using ultrasound, at elevated temperatures, at room temperature or below, , using a combination of room temperature, light, and heating, and on substrates. , Despite a plethora of available methods, to our best knowledge, only two research groups have reported the preparation of highly concentrated silver nanoplate colloids. , Both methods employ a multistep approach by first preparing a blue colloid of silver nanoplate seeds which consequently limited the smallest particle size that can be obtained to 140–150 nm. , The first method employed a flammable solvent acetonitrile, while the second method requires the synthesis of silver thiocyanate, centrifugation, and vacuum drying as necessary intermediate steps . To produce plasmons which cover a broad range of the visible frequencies their size should also be smaller, since beyond crystals of certain size, colloids look typically silvery like bulk silver .…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoplate morphology was first prepared in triangular form by a photoinduced method from synthesized silver nanospheres . Since then, many different synthesis methods have been developed, such as other light irradiation methods, , biomimetic synthesis, and micelle directed synthesis, ,, using ultrasound, at elevated temperatures, at room temperature or below, , using a combination of room temperature, light, and heating, and on substrates. , Despite a plethora of available methods, to our best knowledge, only two research groups have reported the preparation of highly concentrated silver nanoplate colloids. , Both methods employ a multistep approach by first preparing a blue colloid of silver nanoplate seeds which consequently limited the smallest particle size that can be obtained to 140–150 nm. , The first method employed a flammable solvent acetonitrile, while the second method requires the synthesis of silver thiocyanate, centrifugation, and vacuum drying as necessary intermediate steps . To produce plasmons which cover a broad range of the visible frequencies their size should also be smaller, since beyond crystals of certain size, colloids look typically silvery like bulk silver .…”
Section: Introductionmentioning
confidence: 99%
“…Such Ag NCs have been used to localized surface plasmon resonance (LSPR) sensor, surface enhanced Raman spectroscopy (SERS), light management in optoelectronic devices, and templates for hollow structures . Due to the intensive studies, the shape controlled Ag NCs such as nanospheres, nanocubes, nanobars, nanoplates, and nanowires were successfully synthesized by polyol solution chemistry. Among them, the Ag nanocubes have attracted great attention because they can be used as a sacrificial template for hollow Au nanostructure, which can be used as a sensor and a container due to controllable LSPR peaks near infrared region, and a useful substrate for SERS sensing …”
Section: Introductionmentioning
confidence: 99%
“…89 In general, capping ligands are divided into five categories: polymeric ligands, ionic organic ligands, nonionic organic ligands, small molecules, and inorganic ions. Popular polymer ligands include PVP, 90,91 polyoxyethylene (100) stearyl ether (Brij 700), 92 polyethylenimine, 93 polyamine, 94 etc. They have long carbon chains that can prevent particles from coalescing.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 99%